Value co-production through external communication consulting - Kantanen, Helena (Corporate Communications: An International Journal, 2017)
Purpose The purpose of this paper is to examine the prerequisites of value co-production by a communication consultant and workshop participants during a communication improvement programme carried out in a medium-sized family firm. Design/methodology/approach The paper draws from a socio-constructivist view of learning that emphasises participatory processes. It utilises the value co-production concept, referring to collaborative, dialogic activities between the consultant and the client. The theoretical framework includes the transcoder, re-interpreter, and free creator roles of a consultant as realised in a consultancy process characterised by dialogic interaction and equity. The approach is qualitative, and the data come from the expectations of the management team, a video recording of a communication improvement workshop, insights produced in the workshop, and a research journal. Findings The roles of a consultant were found to be those of organiser, transcoder, re-interpreter, and co-creator. Additionally, a dialogue facilitator role was highlighted as a central prerequisite of value co-production. The importance of a positive spirit in consultancy sessions was questioned because problems can thereby be hidden behind positivity. The value of confusing or even destructive episodes was emphasised as a source of new perspectives. Research limitations/implications There are limitations related to the quality of the video recordings, and that the company employees did not yet evaluate the value gained in the long run. Practical implications This paper shows that a communication consultant gains insights from company representatives’ insider views in conflict-management situations, and that these conflicts can be useful for organisational learning. Originality/value This study contributes to research into strategic communication because it provides new knowledge about the consultant-client interface, particularly in value co-production, in the few studies conducted in the context of SMEs. The study utilises the novel research methodology of video analysis.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTEwOC9jY2lqLTAyLTIwMTYtMDAxOQ